Qualitative research writing : credible and trustworthy writing from beginning to end - Salmona, Michelle; Kaczynski, Dan; Lieber, Eli (Thousand Oaks : Sage, 2024)
"The most difficult part of many qualitative research projects is writing it up. What if a book could walk you through the process, step-by-step and help you not only build connections in your research but help you find your writing voice? Thinking and Writing About Qualitative Research can help. This applied, practical book on writing up qualitative research will help you produce strong reports, articles, and proposal to share with you readers. Concrete examples walk you through operationalizing your study, developing your argument, mapping your thinking, and producing a finished product. This text emphasizes the importance of steps to getting started (getting going) and keeping connected (keeping going) to the writing process. In addition, this book will also provide ways to promote engagement by bringing digital tools into the conversation. A final postscript on sharing your research and appreciating the impact of your work help bring joy to the writing process. Turn your qualitative researc into writing with this text"--
Keywords: Social sciences -- Research -- Methodology; Qualitative research -- Data processing